Political stability and the trade-Off theory of capital structure: Evidence from non-financial firms in Palestine - Shawakha, Mahmoud Jamal Ahmad (Edelweiss Applied Science and Technology, 2025)
This study investigates the applicability of the Trade-Off Theory of capital structure in the politically unstable environment of Palestine, emphasizing how political stability moderates the influence of firm-specific financial factors. The analysis uses panel data from 23 non-financial firms listed on the Palestine Exchange over the period 2012–2022. Multiple econometric techniques were employed, including Ordinary Least Squares (OLS), Fixed Effects and Random Effects models, Generalized Method of Moments (GMM), and Quantile Regression, to ensure robust results. The findings reveal a significant negative relationship between profitability and leverage, supporting the Pecking Order Theory under conditions of political uncertainty. Political stability is shown to have a moderating effect, influencing both the magnitude and direction of the relationships between leverage and other firm-level characteristics such as firm size, sales growth, and industry. Capital structure decisions in fragile and conflict-affected economies cannot be fully explained by traditional financial theories alone. Instead, they reflect a complex interaction between internal financial characteristics and external institutional factors. The findings offer valuable insights for policymakers, investors, and corporate managers operating in politically unstable environments, helping them make more informed capital structure decisions under uncertainty.